EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DALAM MELATIH KEMAMPUAN PEMECAHAN MASALAH IPA SISWA KELAS TINGGI SD - Hanatasya Putri Rahman; Salsabila Zahira; Fina Parsyamiati; Alif Nurkholyah; Khoirunnisa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the effectiveness of using series picture media on changes in the state of matter to improve the conceptual understanding of various changes in the state of matter among fourth-grade students at SDN 121/I Muaro Singoan. This research used a pre-experimental method with a one-group pretest-posttest design. The subjects were 19 fourth-grade students. The research instrument used was a student worksheet (LKS) containing series pictures that included melting candles, freezing water, boiling water, condensing clouds, and melting soap, with columns to identify the types of changes. Data were analyzed descriptively and quantitatively by calculating the percentage of learning completeness. The results showed a significant improvement in understanding. In the pretest, only 26.3% of students were able to correctly identify various changes in the state of matter, while in the post-test, this increased to 84.2%. The conclusion of this study is that series picture media on changes in the state of matter is effective in improving the conceptual understanding of changes in the state of matter for fourth-grade students at SDN 121/I Muaro Singoan.